2016
DOI: 10.1016/j.rmed.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of body habitus and respiratory function in Duchenne muscular dystrophy

Abstract: The present study reinforces the importance of weight management in DMD, showing that a higher weight profile and lower adiposity have better respiratory outcomes. Furthermore, attention to body position with airway clearance techniques will maximize their effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
13
1
1
Order By: Relevance
“…Indeed, a significant association was found between serum albumin and respiratory muscle strength. In addition, in DMD, the BMI has been reported to be associated with the respiratory function 34 and the regional lean mass is reduced and associated with decreased strength 35 . We found a significant association between nutritional parameters, namely albumin, prealbumin (transthyretin) and BMI, and respiratory muscle strengths (MIP and MEP).…”
Section: Discussionmentioning
confidence: 54%
“…Indeed, a significant association was found between serum albumin and respiratory muscle strength. In addition, in DMD, the BMI has been reported to be associated with the respiratory function 34 and the regional lean mass is reduced and associated with decreased strength 35 . We found a significant association between nutritional parameters, namely albumin, prealbumin (transthyretin) and BMI, and respiratory muscle strengths (MIP and MEP).…”
Section: Discussionmentioning
confidence: 54%
“…However, it is likely, given the conflicting findings, that any effect on rate of decline in LF is small, and only one Steroid Naïve subject and no Steroid Users underwent spinal surgery. Likewise, the effects of body mass index and fat distribution have been examined for effect on FVC and sleep disordered breathing 25 26. While both spinal deformity and body weight/habitus have the potential to add bias to the current study, the effects are likely to be small, and analysing their contribution would require large patient numbers.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 34 patients with Duchenne muscular dystrophy (DMD, mean age 13.7 years) Chew et al ( Chew et al, 2016 ) found that BMI was positively related to FVC, contrary to what one might expect in obese individuals ( Sharp et al, 1964 ; Thomas et al, 1989 ; Salome et al, 2010 ). The observed association may have been the result of corticosteroid therapy resulting in greater muscle mass and strength, although the study did not take into account changes in muscle and fat mass, edema or growth, also known to occur in DMD ( Durnin and Rahaman, 1967 ; Stanbury and Graham, 1998 ; Pessolano et al, 2003 ).…”
Section: Effects Of Obesitymentioning
confidence: 98%